Community Capacity Building on a Healthy and Child-Friendly Environment Through the Great Parents School (SOTH) Program in Mojolangu Village, Lowokwaru District, Malang City (TEKAD : Teknik Mengabdi, 2025)
SOTH is a program initiated by the National Population and Family Planning Board (BKKBN) that is organized to improve parents' knowledge, attitudes, and skills in parenting. This is to optimize children's growth, development, and positive character, as well as being one of the efforts to reduce stunting, supporting the zero stunting program. Through proper parenting, both physically and psychologically, it is expected to reduce the risk of stunting. One of the physical aspects related to parenting is the child's environment, both outdoor and indoor spaces. A Healthy & Child- Friendly Environment aims to create an environment or space that supports the growth and development of the little ones by providing various positive stimulations. When children can carry out activities safely and comfortably, it will provide energy and freedom for children to be active. For the success of this program, multi-sector collaboration is needed that cares about and can support the sustainability of activities. The Faculty of Engineering, University of Brawijaya, through its Community Service program, in collaboration with Mojolangu Village, actively participates in helping to implement SOTH activities. Through increasing community awareness and understanding about parenting, both physically and psychologically, it will help prevent and overcome stunting so that healthy and quality children are expected to be formed.